2009
DOI: 10.1099/vir.0.005595-0
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus type 5 exploits two different entry pathways in human embryo fibroblasts

Abstract: The helper-dependent adeno-associated viruses (AAVs) have attracted great interest as vectors for gene therapy. Uptake and intracellular trafficking pathways of AAV are of importance, since they are often rate-limiting steps in infection. Here, we have investigated the entry of AAV type 5 (AAV5) in primary human embryo fibroblasts. At low binding temperatures, numerous virions are concentrated between cells, at contact points between cells and cellular protrusions, and at filopodia. When the temperature is rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 43 publications
3
26
0
Order By: Relevance
“…Most parvoviruses are known to use clathrin-mediated endocytosis extensively, if not exclusively. Nevertheless, it was recently shown that AAV5 uses both clathrin and caveolar endocytosis to enter cells (1). Inhibition of caveolae had no effect on PPV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most parvoviruses are known to use clathrin-mediated endocytosis extensively, if not exclusively. Nevertheless, it was recently shown that AAV5 uses both clathrin and caveolar endocytosis to enter cells (1). Inhibition of caveolae had no effect on PPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Caveolar endocytosis is not constitutive and needs to be triggered. This entry mode has been shown to be responsible for simian virus 40 (SV40) infection (37), and among the parvoviruses, only adeno-associated virus 5 (AAV5) is known to use it (1). A third mechanism for virus entry into a cell is macropinocytosis (53).…”
mentioning
confidence: 99%
“…19 As a positive control, we included rAAV5, a serotype capable of entering cells by both clathrin-and caveolin-mediated endocytosis. 20 Although rAAV5 transduction was inhibited by 40% in the presence of genistein, rAAV2-mediated transduction was unaffected and transduction of the capsid insertion mutants was even increased by up to 43% (D5) (Supplementary Figure 1).…”
Section: Non-hspg-binding and Hspg-binding Vectors Use Different Cellmentioning
confidence: 99%
“…1). The receptors for some of the AAV serotypes have been described in the literature (see 6 for a description of the AAV receptors) Receptor-binding is then followed by endocytosis, which for AAV2 is via the so-called CLIC/GEEC (Clathrin Independent Carriers/GPI-anchored protein Enriched Endocytic Compartment) pathway 7 whereas for AAV5 it has been reported that endocytosis can occur both by clathrin coated vesicles or caveolae 8 .…”
Section: Aav Vectors In Cardiovascular Gene Transfermentioning
confidence: 99%